Alternativas ao protocolo ICMP para diagnóstico de estados de hosts e verificação de rotas utilizando software livre - Gugelmin, Daniel (2012)
The purpose of this monograph is to search the reason why it is common and desirable to block the ICMP protocol and to find alternatives using Free Software to perform the main activities of this protocol, such as the ping and the traceroute, executing tests in both an experimental and a prodution network to verify if it is really possible to run such operations as efficiently using the alternative tools.